Chromium-ruthenium oxide solid solution electrocatalyst for highly efficient oxygen evolution reaction in acidic media - Yichao Lin (Nature Portfolio, 2019)
H2 generated from water electrolysis is a promising, carbon-neutral fuel, but sluggish oxidation kinetics and poor catalyst stability in acid limits the chemistry. Here, authors prepare solid-solution catalysts based on ruthenium-chromium oxides that are stable and active for acidic water oxidation.